Field reaction of red fleshed Saccharum robustum against sugarcane borers and termites - Punithavalli, M; Salin, K P; Jebamalaimary, A; Saravanan, L (Indian Journal of Plant Protection, 2022)
Field experiments were conducted to screen the red fleshed Saccharum robustum progenies and along with some popular sugarcane varieties against sugarcane shoot borer, Chilo infuscatellus, internode borer, Chilo sacchariphagus indicus and termites for the two consecutive years (2018-19 and 2019-20) at Sugarcane Breeding Institute, Coimbatore, Tamil Nadu. Among 20 red - fleshed S. robustum progenies screened against shoot borer, 4, 10 and 6 progenies were grouped as tolerance, moderately tolerance and susceptible, respectively. In the progenies, GUK 14-722, GUK 14-130, GUK 14 -129 and GUK 14-745 were recorded 50% incidence of termites whereas